2017
DOI: 10.1136/bmjopen-2017-018094
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with high levels of glycated haemoglobin in patients with type 1 diabetes: a multicentre study in Brazil

Abstract: ObjectiveLong-term complications of type 1 diabetes mellitus (DM1) can be prevented with adequate glycaemic control. However, high levels of glycated haemoglobin (HbA1c) occur in 60%–90% of the patients with DM1. Thus, we aimed to investigate the role of sociodemographic, behavioural and clinical factors on the HbA1c levels of patients with DM1 in Brazil.Design, setting and participantsA cross-sectional study was conducted in ambulatory patients with DM1 aged ≥18 years from 10 Brazilian cities. Sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
8
24
1
1
Order By: Relevance
“…The HbA1c levels were uncontrolled in about 82% of patients enrolled in this study, and our results were in agreement with many studies which reported high HbA1c levels in T2DM …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The HbA1c levels were uncontrolled in about 82% of patients enrolled in this study, and our results were in agreement with many studies which reported high HbA1c levels in T2DM …”
Section: Discussionsupporting
confidence: 93%
“…22 The HbA1c levels were uncontrolled in about 82% of patients enrolled in this study, and our results were in agreement with many studies which reported high HbA1c levels in T2DM. 23,24 Our results showed no correlation between serum Mg level and HbA1c level in contrast to many studies reported that there is an inverse correlation between serum Mg level and HbA1c, 25 some studies showed normal Mg levels in T2DM but lack data correlation to HbA1c.…”
Section: Discussioncontrasting
confidence: 88%
“…[1][2][3][4] Difficulties with insulin dosing and inaccurate dose timing have been shown to result in poor glycemic control for people with diabetes. 5,6 The impact of missed insulin injections on HbA 1c levels is well established, [7][8][9][10][11][12] leading to an increasing risk of diabetes-related complications. 13,14 Technological advances offer opportunities to optimize insulin delivery, reduce dosing errors, and improve regimen management.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 16 children and adolescents with T1DM using another indwelling catheter for insulin administration, Hanas and Ludvigsson found that metabolic control was not altered by the use of the device. 7,8 In the present study, at the end of the 6-month period, 68% of participants (seven from Group A, 10 from Group B) decided to continue with the I-PORT Advance. In contrast, in Group B there was a reduction in HbA1c levels over the 6-month follow-up period, and although there was a slight trend for increasing HbA1c in the second part of the follow-up period (3-6 months), HbA1c remained significantly lower than baseline.…”
Section: Commentmentioning
confidence: 65%
“…Several studies of treatment adherence have been published using data from self-reported questionnaires. 7,8 In the present study, at the end of the 6-month period, 68% of participants (seven from Group A, 10 from Group B) decided to continue with the I-PORT Advance. The reasons for refusing or discontinued use of the device included trouble wearing the device during sport or other social activities.…”
Section: Commentmentioning
confidence: 65%